2022
DOI: 10.1007/s10664-022-10210-w
|View full text |Cite
|
Sign up to set email alerts
|

An empirical evaluation of a novel domain-specific language – modelling vehicle routing problems with Athos

Abstract: Domain-specific languages (DSLs) are a popular approach among software engineers who demand for a tailored development interface. A DSL-based approach allows to encapsulate the intricacies of the target platform in transformations that turn DSL models into executable software code. Often, DSLs are even claimed to reduce development complexity to a level that allows them to be successfully applied by domain-experts with limited programming knowledge. Recent research has produced some scientifically backed insig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…It inspired others to test similar hypotheses using different DSLs, different control and treatment groups, and different assignments. Studies (e.g., [50,[58][59][60]) showed that original hypotheses [49] can be generalized. Indeed, the comprehension correctness and efficiency of DSLs are better than of GPLs.…”
Section: Related Workmentioning
confidence: 99%
“…It inspired others to test similar hypotheses using different DSLs, different control and treatment groups, and different assignments. Studies (e.g., [50,[58][59][60]) showed that original hypotheses [49] can be generalized. Indeed, the comprehension correctness and efficiency of DSLs are better than of GPLs.…”
Section: Related Workmentioning
confidence: 99%
“…DSLs are being used more and more in software development [4][5] [6], as they allow developers to express domain specific concepts in a more natural and easy to understand way. As a result, productivity is increased [7] [8],expressed in the domain concepts in a concise, natural way, facilitating the fulfilment of requirements, error detection, and promotion of changes with greater agility. However, the development of DSLs often requires a significant amount of time and effort, especially when creating a specialized language from scratch [9] [10].…”
Section: Introductionmentioning
confidence: 99%
“…DSLs focus on domain abstractions, which empower end-users to program directly with concepts from the problem domain [4,5]. The benefits of using DSLs are increased flexibility, productivity, reliability, and usability, which have been demonstrated in empirical studies [6][7][8].…”
Section: Introductionmentioning
confidence: 99%